Identifiering och analys av importerade ridhästar i Sverige - von Essen, Ellinor (2019)
As the purpose of horses and riding in Sweden has changed, the breeding has been adapted to the market. In order to develop the Swedish Warmblood horse (SWB), some of the horses used for breeding have been imported from other countries. Horses are also imported for sport purposes, and as these horses can be presumed to be selected for their performance, the genetic evaluation of their fathers may be biased. A previous study has shown that stallions with a large proportion of imported offspring were overvalued, but no consideration was taken to which studbook the horses came from. All horses today have a UELN, a unique ID number, which makes it easier to identify horses across countries. The purpose of this study was to identify imported warmblooded riding horses to find out their country and studbook of origin and to compare performance of horses from different studbooks.